TAXPAYER AWARENESS, TAX SANCTIONS, REPORTING IN TAXPAYER COMPLIANCE UMKM KARANGANYAR - Suprihati Suprihati; Sumartini Sumartini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to determine the effect of taxpayer awareness, tax liability, and taxpayer reporting in Karanganyar, with 100 samples. Methods of data collection using a linkert scale questionnaire. The results showed that tax awareness was related to mandatory compliance in business activity UMKM, sanctions were not related to taxpayer compliance in activity UMKM, and tax reporting on taxpayer compliance who carried out activity UMKM. Keywords: taxpayer, tax liability, reporting, compliance, UMKM